Going off script: Exploring the reporting of preregistration deviations in Industrial and Organizational Psychology and their relationship with questionable research practices - Ann-Kathrin Torka; Joachim Hüffmeier (Journal of Occupational and Organizational Psychology, 2025)
In the present study, we aim to take stock of, encourage and contribute to the establishment of preregistration as a standard to increase transparency in Industrial and Organizational Psychology (IOP). To do so, we examined to what extent IOP research is preregistered and adheres to preregistrations. We analysed 27 IOP journals and found that only 91 articles (0.70% of studies published between 2017 and 2023) included a preregistration. A random sample of 25 of these preregistered studies revealed that 72% deviated from their preregistrations at least once, with 68% having at least one undisclosed deviation, indicating that deviations from preregistrations are common. The studies in our IOP sample deviated on average M 0.167em=0.167em1.84 ( SD 0.167em=0.167em1.72) times from their preregistrations. Importantly, the vast majority of these deviations do not seem to be linked to questionable research practices. We further compared the IOP sample with a recent sample from Psychological Science , which represents the current state-of-the-art in preregistrations. We found no difference in the number of (undisclosed) deviations, which suggests that preregistration can be effectively implemented even in fields where it is not yet standard. To support this implementation, we offer resources and best practice recommendations for transparently reporting deviations.
Keywords: 650; Industrial and Organizational Psychology; Open Science; preregistration; questionable research practices; transparency